(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Purpose: To assess serum tumor necrosis factor-alpha (TNF-α) and interleukin-1β (IL-1β) levels in patients with retinal nerve fiber layer (RNFL) thinning in uveitis complicated by optic nerve inflammation. Material and Methods: One hundred and thirty-two patients underwent examination and treatment. Serum TNF-α and IL-1β levels were determined by commercially available enzyme-linked immunoassay kits. Results: The serum TNF-α level was more than 1.5 times higher in patients with uveitis complicated by optic nerve inflammation who had reduced RNFL thickness compared to patients with normal RNFL thickness (p < 0.05), and the serum IL-1β level was 17% higher in the former patients than in the latter patients (p > 0.05). Conclusion: In the active stage of uveitis, the serum TNF-α level was significantly higher in patients with RNFL thinning due to uveitis complicated by optic nerve inflammation compared to patients with normal RNFL thickness, and the serum IL-1β level was higher in the former patients than in the latter patients, but the difference was not statistically significant. The results of the study may justify the use of biologic therapy in the treatment of uveitis complicated by optic nerve inflammation.